Optimalisasi Soft Skill Pada Lembaga Pendidikan Di Era 4.0 - Irawan, Andri; Setiawati, Tia; Andiana, Anisa (Journal of Comprehensive Science, 2023)
The purpose of this research is to examine and describe the results of research on Soft Skills in Indonesia, especially in the scope of educational institutions. From these findings, it is used as a basis for finding new ways, especially to optimize Soft Skills in Educational Institutions. The research method uses content analysis of articles from 2015-2022 from the Google Schoolar, Scopus.com and Garuda sites which are searched using the keyword "Soft Skill". The research findings show the diversity of optimizing Soft Skills in various Educational Institutions which provides its own challenges for teachers in implementing Soft Skill optimization in the 4.0 era. Thus the teacher needs to apply suitable learning activities to optimize Soft Skills. The new way that teachers can implement, especially in optimizing Soft Skills in Educational Institutions in the 4.0 era, is an effective learning process, carrying out various kinds of training, inserting an understanding of Soft Skills in each learning process using various methods such as project based learning, implementing character education programs students through teaching factory (TEFA), namely research that recommends the application of soft skills by means of product-based learning models (goods/services) through school and industry synergies to produce graduates who are competent according to industry needs.